Temperature dependence on VUV-absorption cross sections of CO2 molecule in the energy region of 10.6 – 11.8 eV. (August 2015) - Hoshino, M; Matsui, M; Mochizuki, Y; Odagiri, T; Kondo, A; Shigemura, K; Kitajima, M; Watanabe, N; Adachi, J; Limão-Vieira, P; Tanaka, H
Synopsis: We have developed a new setup to measure temperature dependence on vacuum ultraviolet absolute photoabsorption cross sections for linear triatomic molecules from room temperature (∼300 K) up to 700 K. The setup consists of a stainless steel absorption-cell wrapped by sheath wires of 1.2φ in diameter and 2 m length. For the first set of measurement on CO2 in the photon energy range 10.6 – 11.8 eV, we found that the cross section values at room temperature are in very good agreement with previous measurements as well as the temperature dependence on the cross sections are clearly observed in the measured temperature range.